PENGARUH KUALITAS PELAYANAN, KEPUASAN TAMU, DAMPAKNYA TERHADAP NIAT DATANG KEMBALI PADA INTERCONTINENTAL RESORT - I Nyoman Sedana; Lukia Zuraida; I Putu Utama (Tulisan Ilmiah Pariwisata (TULIP), 2024)
This study aims to determine the effect of service quality on satisfaction and intention to return to Resort guests by using a accidental sampling technique on 160 respondents which were then analyzed using Structural Equation Models (SEM) via Smart-Pls. The results of the study state that 1) service quality has a significant positive effect on customer satisfaction. Where the coefficient is 0.960. 2) customer satisfaction has a positive and insignificant effect on intention to return Where the coefficient is 0.162. 3) service quality has a positive and significant effect on intention to return, Where the coefficient is 0.771. 4) Testing the mediation effect with the VAF value obtained at 16.74% so that there is no mediation effect by the customer satisfaction variable on the relationship between service quality and intention to return. The Resort needs to maintain service quality through the provision of the latest facilities (up to date), improve performance so that services are provided on time so as to maintain guest satisfaction and intention to come back to the InterContinental Bali Resort.